(untitled) (Journal of Monno Medical College, 2023)
Background: After suicidal poisoning, death due to hanging is one of the common modes of suicide encountered in medico-legal procedure in Bangladesh. Objective: To study on demographic and autopsy findings associated with suicide by hanging at Manikganj district, Bangladesh. Methodology: This retrospective cross-sectional study was conducted in the District hospital, Manikganj, Bangladesh during the period of January 2019 to December 2020. Results: A total of 381 medico-legal autopsies were analyzed, out of which 169 were deaths due to hanging. Out of 169 cases, the maximum (69, 40.8%) deaths were due to hanging in the age group of 21-30 years. Majority (101, 59.8%) of the cases were observed in females and among them, maximum were housewives (60, 35.5%). Most of the death bodies (47, 27.81%) were brought from Manikganj police station. Regarding the ligature material used, majority (133, 78.7%) of victims had used soft ligature material, like Dopatta (orhna) (56, 33.1%). Considering the autopsy findings, cyanosis of fingertips and nail bed was the commonest (163, 96.4%), followed by subcutaneous tissue under the ligature mark found pale, white, hard and glistening (159, 94.0%), and dribbling mark of saliva in case of asphyxial death due to hanging (144, 85.2%). Conclusion: Suicidal hanging was commonly encountered in younger age group and in many cases of financial problem, followed by family disputes were commonly observed. J Monno Med Coll June 2022;8(2): 31-35